Design of Large Field-of-View High-Resolution Miniaturized Imaging System. (2nd July 2007) - Ahuja Ahuja, Nilesh A. Nilesh A.; Bose Bose, N. K. N. K.
Abstract : Steps are taken to design the optical system of lenslet array/photoreceptor array plexus on curved surfaces to achieve a large field of view (FOV) with each lenslet capturing a portion of the scene. An optimal sampling rate in the image plane, as determined by the pixel pitch, is found by the use of an information theoretic performance measure. Since this rate turns out to be sub-Nyquist, superresolution techniques can be applied to the multiple low-resolution (LR) images captured on the photoreceptor array to yield a single high-resolution (HR) image of an object of interest. Thus, the computational imaging system proposed is capable of realizing both the specified resolution and specified FOV.